Reactive, Adult Neurogenesis From Increased Neural Progenitor Cell Proliferation Following Alcohol Dependence in Female Rats - Nawarawong, Natalie N.; Thompson, K. Ryan; Guerin, Steven P.; Anasooya Shaji, Chinchusha; Peng, Hui; Nixon, Kimberly (Frontiers in Neuroscience, 2021)
Hippocampal neurodegeneration is a consequence of excessive alcohol drinking in alcohol use disorders (AUDs), however recent studies suggest that females may be more susceptible to alcohol-induced brain damage. Adult hippocampal neurogenesis is now well accepted to contribute to hippocampal integrity and is known to be affected by alcohol in humans as well as in animal models of AUDs. In male rats, a reactive increase in adult hippocampal neurogenesis has been observed during abstinence from alcohol dependence, a phenomenon that may underlie recovery of hippocampal structure and function. It is unknown whether reactive neurogenesis occurs in females. Therefore, adult female rats were exposed to a four-day binge model of alcohol dependence followed by seven or fourteen days of abstinence. Immunohistochemistry was used to assess neural progenitor cell (NPC) proliferation (BrdU and Ki67), the percentage of increased NPC activation (Sox2+/Ki67+), the number of immature neurons (NeuroD1), and ectopic dentate gyrus granule cells (Prox1). On day seven of abstinence, ethanol-treated females showed a significant increase in BrdU+ and Ki67+ cells in the subgranular zone of the dentate gyrus (SGZ), as well as greater activation of NPCs (Sox2+/Ki67+) into active cycling. At day 14 of abstinence, there was a significant increase in the number of immature neurons (NeuroD1+) though no evidence of ectopic neurogenesis according to either NeuroD1 or Prox1 immunoreactivity. Altogether, these data suggest that alcohol dependence produces similar reactive increases in NPC proliferation and adult neurogenesis. Thus, reactive, adult neurogenesis may be a means of recovery for the hippocampus after alcohol dependence in females.